Modeling safety risk perception due to mobile phone distraction among four wheeler drivers. (April 2017) - Rajesh, Raghunathan; Srinath, R.; Sasikumar, R.; Subin, B.
Abstract: Nowadays, there is an increasing trend in the use of information and communication technology devices in new vehicles. Due to these increasing service facilities, driver distraction has become a major concern for transportation safety. To reduce safety risks, it is crucial to understand how distracting activities affect driver behavior at different levels of vehicle control. The objective of this work is to understand how the vehicle and driver characteristics influence mobile phone usage while driving and associated risk perception of road safety incidents. Based on literature review, a man–machine framework for distracted driving and a mobile phone distraction model is presented. The study highlights the findings from a questionnaire survey conducted in Kerala, India. The questionnaire uses a 5-point Likert scale. Responses from 1203 four-wheeler drivers are collected using random sampling approach. The questionnaire items associated with three driver-drive characteristics are: (i) Human Factors (age, experience, emotional state, behavior of driver), (ii) Driver space (meter, controls, light, heat, steering, actuators of vehicle), (iii) Driving conditions (speed, distance, duration, traffic, signals). This mobile phone distraction model is tested using structural equation modeling procedure. The study indicates that among the three characteristics, 'Human Factors' has the highest influence on perceived distraction due to mobile phones. It is also observed that safety risk perception due to mobile phone usage while driving is moderate. The practical relevance of the study is to place emphasis on behavior-based controls and to focus on strategies leveraging perception of distraction due to mobile phones while driving. Highlights: Distracted mobile driving model is proposed. Structural equation modeling approach was used to test hypothesis. Human factors influenced mobile phone distraction perception. Strong mobile phone distraction perception causes negative risk perception. Mobile phone distraction mitigates mobile use.